1991
DOI: 10.1111/j.1570-7458.1991.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of fertilizer regime with host‐plant resistance in tomato

Abstract: The effect of fertilizer regime on trichome‐ and lamellar‐based resistance in the wild tomato species, Lycopersicon hirsutum f. glabratum C. H. Mull accession PI 134417, to three insect pests of tomato, the tobacco hornworm, Manduca sexta (L.), the Colorado potato beetle, Leptinotarsa decemlineata (Say), and the tomato fruitworm, Heliocoverpa zea (Boddie), was examined. Increasing the rate at which NPK fertilizer was applied, from 1.8 to 19.6 g/plant/week, reduced the trichome‐based resistance of PI 134417 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
3
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
0
23
3
2
Order By: Relevance
“…It also has been demonstrated that addition of protein to diets containing o~-tomatine increases the growth rates of L. decemlineata larvae compared to the growth rates of larvae fed a similar diet containing ot-tomatine but without additional protein (Hare, 1987). Both the trichome-and lamellar-based resistance of PI 134417 can be reduced dramatically by increasing the rate and/or frequency of fertilizer applications (Barbour et al, 1990; see also Dodds, 1987 andJanssen andSmilowitz, 1986a,b for similar work in tomato and potato, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…It also has been demonstrated that addition of protein to diets containing o~-tomatine increases the growth rates of L. decemlineata larvae compared to the growth rates of larvae fed a similar diet containing ot-tomatine but without additional protein (Hare, 1987). Both the trichome-and lamellar-based resistance of PI 134417 can be reduced dramatically by increasing the rate and/or frequency of fertilizer applications (Barbour et al, 1990; see also Dodds, 1987 andJanssen andSmilowitz, 1986a,b for similar work in tomato and potato, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…However, in the high-yielding areas, such as the Yangtze Delta area, the usage of nitrogenous fertilizer could be 270-300 kg per ha and here the recovery efficiency for N is only about 20 % (Peng et al 2002;Li and Tang 2006). Heavy applications of nitrogenous fertilizer may not affect insect biology directly but bring about changes in host plant morphology, biochemistry, and physiology, which could improve the plant's nutritional condition for herbivores and reduce host resistance to them (Barbour et al 1991). Thus, the excessive use of nitrogenous fertilizers creates favorable food conditions for rice planthoppers.…”
Section: High Nitrogen Fertilizer Inputsmentioning
confidence: 98%
“…Host plant rearing was regulated so as to limit the variation in plant phenological effects (e.g. changes in fertiliser regime [Barbour et al, 1991] and differences in leaf age [e.g. Noldus et al, 1986b].…”
Section: Introductionmentioning
confidence: 99%